Evidence for a protective effect of the loss of α4-containing nicotinic acetylcholine receptors on Aβ-related neuropathology in Tg2576 mice - Vilella, Antonietta; Romoli, Benedetto; Bodria, Martina; Pons, Stéphanie; Maskos, Uwe; Zoli, Michele (Frontiers in Neuroscience, 2023)
Loss of cholinergic neurons as well as α4β2* (*=containing) nicotinic acetylcholine receptors (nAChRs) is a prominent feature of Alzheimer’s disease (AD). Specifically, amyloid β (Aβ), the principal pathogenic factor of AD, is a high affinity ligand for nAChRs. Yet, the pathophysiological role of nAChRs in AD is not well established. In the present study, we have investigated the effects of the loss of α4* nAChRs on the histological alterations of the Tg2576 mouse model of AD (APPswe) crossing hemizygous APPswe mice with mice carrying the genetic inactivation of α4 nAChR subunit (α4KO). A global decrease in Aβ plaque load was observed in the forebrain of APPswe/α4KO mice in comparison with APPswe mice, that was particularly marked in neocortex of 15 month-old mice. At the same age, several alterations in synaptophysin immunoreactivity were observed in cortico-hippocampal regions of APPswe mice that were partially counteracted by α4KO. The analysis of the immunoreactivity of specific astroglia (glial fibrillary acidic protein, GFAP) and microglia (ionized calcium-binding adapter molecule, Iba1) markers showed an increase in the number as well as in the area occupied by these cells in APPswe mice that were partially counteracted by α4KO. Overall, the present histological study points to a detrimental role of α4* nAChRs that may be specific for Aβ-related neuropathology.